2011
DOI: 10.1590/s1516-05722011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Efeito embriotóxico, teratogênico e abortivo de plantas medicinais

Abstract: RESUMO: O uso milenar de plantas medicinais mostrou ao longo dos anos, que determinadas plantas apresentam substâncias potencialmente perigosas. Do ponto de vista científico, algumas pesquisas mostraram que muitas dessas plantas possuem substâncias agressivas e por essa razão devem ser utilizadas com cuidado, respeitando seus riscos toxicológicos. Os efeitos mais preocupantes do uso indiscriminado de plantas medicinais são embriotóxico, teratogênico e abortivo, uma vez, que os constituintes da planta podem atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
32

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 26 publications
(25 reference statements)
0
14
0
32
Order By: Relevance
“…Despite the therapeutic advantages of medicinal plants, their potential toxicity is not recognized by the general public or by many professional groups of traditional medicine (SOETAN; AIYELAAGBE, 2009). Many plant species commonly considered medicinal can contain potentially dangerous substances (RODRIGUES et al, 2011;MELO-REIS et al, 2011). Recent research studies conducted in vitro and in vivo revealed that many plants used as food or in traditional medicine have cytotoxic and genotoxic effects (SEHGAL et al, 2006;DALLA NORA et al, 2010;CARDOSO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the therapeutic advantages of medicinal plants, their potential toxicity is not recognized by the general public or by many professional groups of traditional medicine (SOETAN; AIYELAAGBE, 2009). Many plant species commonly considered medicinal can contain potentially dangerous substances (RODRIGUES et al, 2011;MELO-REIS et al, 2011). Recent research studies conducted in vitro and in vivo revealed that many plants used as food or in traditional medicine have cytotoxic and genotoxic effects (SEHGAL et al, 2006;DALLA NORA et al, 2010;CARDOSO et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the therapeutic advantages of medicinal plants, their potential toxicity has not been recognized by the general public or by professional groups of traditional medicine (Soetan and Aiyelaagbe, 2009), and many plant species commonly considered medicinal can contain potentially dangerous substances (Rodrigues et al, 2011). Recent research studies conducted in vitro and in vivo assay have revealed that many plants used as food or in traditional medicine have cytotoxic and genotoxic effects (Sehgal et al, 2006;Dalla Nora et al, 2010;Luz et al, 2012;Ping et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most worrying effects of the indiscriminate use of medicinal plants are embryotoxic, teratogenic and abortifacient, once the constituents of plants can cross the placenta and reach the fetus. 19 The plants cited as potentially toxic Arnica montana L., Artemisia vulgaris L., Stryphnodendron polyphyllum Mart., Vernonia condensata Baker, Echinodorus macrophyllus (Kunth) Micheli, Phyllanthus amarus Schumach. & Thonn., Mentha piperita L., among others.…”
Section: Discussionmentioning
confidence: 99%